Integrating EVs into distribution grids: Examining the effects of various DSO intervention strategies on optimized charging - Arne Lilienkamp; Nils Namocke (Institute of Energy Economics at the University of Cologne (EWI), 2024)
Adopting electric vehicles (EVs) and implementing variable electricity tariffs increase peak demand and the risk of congestion in distribution grids. To avert critical grid situations and sidestep expensive grid expansions, Distribution System Operators (DSOs) must have intervention rights, allowing them to curtail charging processes. Various curtailment strategies are possible, varying in spatio-temporal differentiation and possible discrimination. However, evaluating different strategies is complex due to the interplay of economic factors, technical requirements, and regulatory constraints - a complexity not fully addressed in the current literature. Our study introduces a sophisticated model to optimize electric vehicle charging strategies to address this gap. This model considers different tariff schemes (Fixed, Time-of-Use, and Real-Time) and incorporates DSO interventions (basic, variable, and smart) within its optimization framework. Based on the model, we analyze the rexibility demand and total electricity costs from the users' perspective. Applying our model to a synthetic distribution grid, we îond that rexible tariffs offer consumers only marginal economic benefits and increase the risk of grid congestion due to herding behavior. All curtailment strategies effectively alleviate congestion, with variable curtailment featuring spatio-temporal differentiation, approaching optimality regarding rexibility demand. Notably, applying curtailment from the users' perspective does not lower cost savings significantly.
Keywords: C61; D47; Q41; Q48; 330; Distribution Grid; Electric Vehicles; Smart Charging; Flexibility